A case of HIV ulcer. (7th July 2015) - Weledji, Elroy Patrick
HIV-associated ulcers must be distinguished from idiopathic anal fissures in HIV-positive patients and from other sexually transmitted diseases that cause anogenital ulcers as the treatments differ.